Higher-Order Attribute Semantics of Flat Declarative Languages - Grigorenko, Pavel; Tyugu, Enn (Computing and Informatics, 2012)
A technique is described that provides a convenient instrument for implementation of semantics of simple declarative languages called flat languages. Semantics of a specification is defined in the paper as a set of programs derivable for solvable goals. We introduce higher-order attribute models that include more control information than conventional attribute models and explain the algorithm for dynamic evaluation of attributes on these models. A visual tool CoCoViLa is briefly described as an instrument for implementing attribute semantics of flat languages.